Narcissus and Eros on the cross of the present - Drivet, Leandro (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
The author presents a review of the following book:  Abadi, Florencia. (2018). El sacrificio de Narciso. Hecho Atómico Editores, 91 pages.